STRATEGIES FOR ENHANCING WORK MOTIVATION OF GENERATION Z NURSE: NURSING LEADERSHIP ROLE - จึงพิภานิชกุล, ศุภกฤต; ฉันทนารุ่งภักดิ์, โฆษิต (Primary Health Care Journal (Northeastern Edition), 2026)
Professional nurses constitute a vital segment of the healthcare workforce, accounting for approximately 78.0% of all public health personnel. As frontline providers of direct patient care, their performance significantly influences service quality, organizational success, and survival. Currently, the healthcare system is welcoming a new wave of professionals known as Generation Z nurses (born since 1997). Raised in an era of rapid technological advancement, this cohort faces unique challenges regarding adaptation, heavy workloads, and the need for resilience to achieve professional goals. Therefore, formulating effective motivation strategies is crucial. This academic article aims to analyze strategies for enhancing the motivation of Generation Z nurses, grounded in Maslow’s Hierarchy of Needs and leadership concepts. Based on a review of the literature, this paper proposes practical strategies that integrate Maslow’s theory with the role of nursing leaders. These insights serve as a guideline for nursing administration to effectively manage personnel and foster a motivated workforce within healthcare organizations.